2017
DOI: 10.1016/j.bmc.2017.06.046
|View full text |Cite
|
Sign up to set email alerts
|

New prodrugs of two pyrimidine acyclic nucleoside phosphonates: Synthesis and antiviral activity

Abstract: New 2,4-diamino-6-[2-(phosphonomethoxy)ethoxy]pyrimidine (PMEO-DAPy) and 1-[2-(phosphonomethoxy)ethyl]-5-azacytosine (PME-5-azaC) prodrugs were prepared with a pro-moiety consisting of carbonyloxymethyl esters (POM, POC), alkoxyalkyl esters, amino acid phosphoramidates and/or tyrosine. The activity of the prodrugs was evaluated in vitro against different virus families. None of the synthesized prodrugs demonstrated activity against RNA viruses but some of them proved active against herpesviruses [including her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Krecmerová and co‐worker in 2017, stated the synthesis and anti‐viral activity of some acyclic nucleoside phosphonates ( 112 ) [5] . Anti‐viral and cytotoxicity properties of the synthesized compounds were studied, and one of the compounds 112 (Figure 13), came out as highly active and selective PME‐5‐azaC (1‐[2‐(phosphonomethoxy) ethyl]‐5‐azacytosine) prodrug against Varicella zoster virus, Herpes simplex virus and Human cytomegalovirus with EC 50 values ranging 0.15–1.12 mM.…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Krecmerová and co‐worker in 2017, stated the synthesis and anti‐viral activity of some acyclic nucleoside phosphonates ( 112 ) [5] . Anti‐viral and cytotoxicity properties of the synthesized compounds were studied, and one of the compounds 112 (Figure 13), came out as highly active and selective PME‐5‐azaC (1‐[2‐(phosphonomethoxy) ethyl]‐5‐azacytosine) prodrug against Varicella zoster virus, Herpes simplex virus and Human cytomegalovirus with EC 50 values ranging 0.15–1.12 mM.…”
Section: Pharmacologymentioning
confidence: 99%
“…The symmetrical shape of the s ‐triazine is one of the major reasons responsible for its excellent biological profile. The s ‐triazine ring provides exceptional framework for the design of biologically potent molecules with broad clinical variabilities like anti‐protozoa, [3] anti‐cancer, [4] anti‐viral, [5] anti‐microbial [6] and many more as summarized in Figure 2. It is also the basic structure of some herbicides like amitole, atrazine, cyanazine, simazine, trietazine, and resin modifiers like melamine and benzoguanamine [7] .…”
Section: Introductionmentioning
confidence: 99%
“…From the pharmacologic perspective, nitrogenous bases are investigated as pharmacophores and are found in the structure of many drugs and experimental substances with various activities, 85 such as antitumoral, 86 antibacterial, 87 antiparasitic, 88 and antiviral. 89 , 90
Fig. 3 Chemical structures of pyrimidine nitrogenous bases cytosine (5), uracil (6) and thymine (7) and pyrimidine derivatives drugs: 5-Fluorouracil (8) ; Gemcitabine (9) ; Baricitinib (10) ; Sunitinib ( 11 ); Erlotinib (12); Galidesivir ( 13 ); Sofosbuvir ( 14 ); Telbivudine ( 15 ).
…”
Section: Drug Repurposing For Covid-19mentioning
confidence: 99%
“…This format solves issues of high polarity in its final structure prompted by the phosphonic acid, which interferes with pharmacological properties and causes low cellular permeability and low oral bioavailability. 90 …”
Section: Drug Repurposing For Covid-19mentioning
confidence: 99%
“…9 The majority of the commercially available drugs are built on heterocyclic scaffolds and these chemical fragments are responsible for desired pharmacological activity. 10 Pyrimidine, a six membered heterocyclic ring with nitrogen atom, exhibits various pharmacological activities such as anticancer, [11][12][13] antimicrobial, 14,15 antiviral, [16][17][18] anti-tubercular, 19,20 anti-inammatory, 21,22 antimalarial, 23,24 anti-diabetic 25 and antipyretic. 26 Among these diverse pyrimidine derivatives, amino-pyrimidine plays a vital role in the therapeutic activities against cancers, meanwhile, a large number of studies have been reported in recent years.…”
Section: Introductionmentioning
confidence: 99%